Enantioselective Total Synthesis of the Proposed Structure of the Endophytic Fungal Metabolite Phomolide G: Structural Revision and Unambiguous Stereochemical Assignment. Issue 4 (15th January 2016) - McNulty, James; McLeod, David; Jenkins, Hilary A.
Abstract: A total synthesis of the proposed structure of the natural macrolactone phomolide G (1 ) by a bidirectional strategy fromL ‐tartaric acid is reported. The ω‐terminus of the molecule was elaborated by nitrile extension, C3‐alkylation and a substrate‐controlled 1, 3‐ketone reduction. The α‐terminus was extended by a C2 aldehyde‐to‐alkenal homologation followed by an auxiliary controlled aldol reaction. Macrolactonization and deprotection yielded compound1 (confirmed by X‐ray analysis). This putative structure of phomolide G displayed discordant NMR spectroscopic data in comparison with those of the natural product. Detailed inspection of all NMR spectroscopic data available indicated phomolide G to be likely a diastereomer of1 . The synthetic strategy developed allows control of the absolute stereochemistry at all four chiral secondary alcohol groups. Further manipulation allowed for the preparation of diastereomer33, the 1 H and 13 C NMR spectroscopic data of which are in full accord with that reported for the natural product. Abstract : A total synthesis of the proposed structure of the natural macrolactone Phomolide G by a bidirectional strategy fromL ‐tartaric acid is reported. Its structure was confirmed by X‐ray analysis and chemical correlations, which did not match the data of natural Phomolide G. Modifications to this synthesis allowed access to the C3‐epimer, the 1 H and 13 C NMR spectroscopic data of which are in full accord with that reported for the natural product.